بنية الشخصــية في رواية " الناجون " لزهرة رميج - دبيلو, اكرام; حويذق, سارة; طيباني, شيماء (جامعة الوادي - University of Eloued, 2023)
في الأخير نقول أن الرواية من أكثر الاجناس الأدبية استيعابا للواقع ومتغيراته ، فإرتكزت على عنصر مهم وهو الشخصية التي كانت محط درستنا حيث أن الشخصية مكون أساسي في دور الرواية الشخصية أي هي محور المرتكز ، وأهم عناصرها ، حيث تمثل هنا شخصيات حقيقية تعكس جانبا فكريا تعبر عن الوعي ما ينقل عبرها أو بواسطتها إلى المتلقي ، وفهمها يتوقف على فهم دور كل شخصية وما لعبته وكيف ساهمت في تحريك الاحداث خاصة الرئيسية منها : * أسماء كثيرة لعديد من الشخصيات من بلدان مختلفة من خلال الرواية ومن نفس البلد وهي المغرب بالإضافة إلى إهتمامها بأفعال الشخصيات ومشاعرها نظرا لإحتواء الرواية عدد أكبر من الاحداث بما أن قد تمركز عملنا حول التركيز عن الشخصية الروائية ونخلصها كالاتي : توصلنا الى مفهوم البنية ، الذي أثار جدال بين النقاد والدارسين حول مفهومه اللغوي والاصطلاحي لينهي جان بياجيه هذه الانتقادات بمفهوم موحد للبنية . Résumé : فرنسية أو انجلزية In the end, we say that the novel is one of the most literary genres that absorbs reality and its variables, so it was based on an important element, which is the character that was the focus of our study, as the character is an essential component in the role of the personal novel, i. Awareness is what is conveyed through or through it to the recipient, and understanding it depends on understanding the role of each character, what they played, and how they contributed to moving events, especially the main ones: * Many names of many characters from different countries through the novel and from the same country, which is Morocco, in addition to her interest in the actions and feelings of the characters due to the novel containing a greater number of events Since our work has centered around focusing on the fictional character, we conclude it as follows: We reached the concept of structure, which sparked controversy among critics and scholars about its linguistic and idiomatic concept. Jean Piaget ended these criticisms with a unified concept of structure.
ادب حديث ومعاصر
Keywords: بنية الشخصية - رواية - الزهرة رميج - الناجون; The Structure of Personality - A Novel - Al-Zahra Rameej - The Survivors